Structural features of ultrafine zirconia as probed by synchrotron X-ray diffraction; Doklady Physical Chemistry; V. 377, №. 4-6 - Shevchenko V. Ya.; Khasanov O. L. Oleg Leonidovich; Yur'ev G. S.; Pokholkov Y. P. Yuri Petrovich (2001, 2001)
В фонде НТБ ТПУ отсутствует